(untitled) (Journal of Comparative & International Higher Education, 2022)
The experiences of international scholars in the United States who are part of short-term or exchange programs remain vastly under-investigated compared to their full-time, tenure-track, and tenured peers. Gauded by Blau’s (1964) social exchange theory, this study investigated professional and social experiences of exchange scholars at a large public research university in the southeast. Mixed-method exploration was conducted through surveys and individual interviews with international scholars who participated in the exchange program in spring 2020. The results revealed that exchange scholars were most satisfied with work conditions and research experience, but least satisfied with professional development opportunities and cultural exchange. Further, participants’ research experience was significantly correlated with their cultural exchange, while their professional development was significantly correlated with work conditions and support. Additional implications and recommendations were drawn from the results revealing the unmet needs of program participants regarding the different areas of their exchange experiences.